Digital Marketing-Based Business Management Strategy for MSMEs in Luwuk City - Arafah Pandjo, Siti; Lalangi, Febrian; Afriani Ismail, Rindi; Lailatul Nikmah, Fika; Rahman, Wahyudin (Yayasan Pendidikan Belajar Berdikari, 2025)
This study aims to analyze the implementation of digital marketing-based business management strategies among Micro, Small, and Medium Enterprises (MSMEs) in Luwuk City, Indonesia. The research was conducted to understand how MSMEs adopt digital tools to improve competitiveness, customer engagement, and business performance in the digital era. Using a qualitative research design, data were collected through in-depth interviews, field observations, and documentation involving 10 MSME owners from various sectors, including culinary, fashion, handicrafts, and services.The findings show that most MSMEs in Luwuk City have started integrating digital marketing platforms, particularly Facebook, Instagram, and WhatsApp Business, into their promotional strategies. Eight out of ten informants actively use social media to increase visibility and customer interaction, while only three have ventured into e-commerce platforms such as Tokopedia and Shopee due to logistical and payment challenges. The study also reveals that MSMEs adopting digital tools consistently experience sales growth, enhanced brand recognition, and improved management efficiency. However, obstacles such as limited digital literacy, unstable internet infrastructure, lack of advertising budgets, and minimal institutional support remain significant barriers. Digital marketing adoption has encouraged MSMEs to shift from traditional to more structured business management practices, supported by better record-keeping and customer communication. The study concludes that strengthening digital skills, strategic planning, and collaboration among stakeholders is essential to optimize MSME competitiveness in Luwuk City.